Research on AIGC Technology Driven Innovation Models and Risk Management in the Financial Sector - Gong Lipeng (SHS Web of Conferences)
With the rapid development of AI Generated Content (AIGC) technology, its application in the financial field is gradually deepening, bringing new impetus to financial innovation. However, the application of AIGC technology also comes with potential risks, such as data security, algorithm bias, and market manipulation. This article explores the innovative models of AIGC technology in the financial industry based on its core characteristics, including intelligent investment advisory, risk assessment, quantitative trading, financial marketing, and analyzes the risk management challenges it brings. Finally, this article proposes strategies such as improving the regulatory system, optimizing algorithm transparency, and strengthening data governance to promote the healthy development of AIGC technology in the financial sector.